Integrasi Ubudiyah dan Social Emotional Learning (SEL) Berbasis Aswaja: Strategi Pembentukan Karakter Tangguh di Madrasah Ibtidaiyah: Strategi Pembentukan Karakter Tangguh di Madrasah Ibtidaiyah - Tina Annisa, Hikmah Khofia (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2025)
This study examines the integration of ubudiyah practices, Ahlussunnah wal Jamaah (Aswaja) values, and Social Emotional Learning (SEL) competencies in shaping resilient character among students at Madrasah Ibtidaiyah. Using a qualitative case study approach at MI Mambaul Ulum Malang, data were collected through observation, interviews, and documentation, then analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings indicate that ubudiyah activities are not merely ritualistic but also serve as a medium for internalizing spiritual values, discipline, and socio-emotional skills. The integration of the five core SEL competencies with the four Aswaja principles (tawassuth, tawazun, tasamuh, and i’tidal) gives rise to a character education model that is moderate, adaptive, and resilient. This strategy is reinforced through curriculum integration, consistent worship habituation, observation-based evaluation, and teacher role modeling. Despite challenges such as limited teacher understanding and inadequate facilities, this model shows strong potential for broader replication within Islamic education.